(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMARIO: 1. Introducción - 2. Régimen jurídico-constitutivo de iglesias, confesiones y comunidades religiosas - 2.1. La legislación específica de iglesias, confesiones y comunidades religiosas - 2.2. ¿Es de aplicación a las entidades religiosas ‘mayores’ la denominada garantía común asociativa? - 3. Régimen jurídico-constitutivo de asociaciones religiosas - 3.1. Antecedentes - 3.2. Problemática jurídica que plantea esta doble regulación normativa - 3.2.1. ¿Qué diferencias existen entre estos dos regímenes jurídicos, aptos en sus respectivos ámbitos de aplicación, en la regulación y constancia registral del fenómeno asociativo-religioso? - 3.2.2. ¿Resulta ajustado a Derecho este régimen diferenciado, o se constituye en inconstitucional por causante de discriminación? - 3.2.3. ¿Es necesario este doble y distinto régimen jurídico-asociativo? - 4. Epílogo. Associations in the framework of state legal personality of religious organisations in Spain ABSTRACT: The community dimension of religious freedom entails the existence of Churches, Denominations and Religious communities. This paper addresses the issue of whether these entities are applied the common associative guarantee of Article 22 of the Spanish Constitution and, if applicable, the Organic Law on the right of association. The conclusion reached is that religious denominations are not legally considered associations of constitutional relevance. The paper also tackles the scope of application of this Organic Law on the right of association to religious ‘associations’ per se. The study notes they have a different legal regime, due to them being subject to this Law exclusively or to the Organic Law on religious freedom.